THE EFFECT OF NONI (MORINDA CITRIFOLIA L.) LEAVES EXTRACT ON BRUISES HEALING AMONG PERSAUDARAAN SETIA HATI TERATE MARTIAL ARTS ATHLETES - Hidayati, Nur; Prasetiyo, Muhammad; Rokhman, Abdul (Universitas Airlangga, 2024)
Introduction: Bruises are the most common injuries for martial arts athletes during training and competitions. If bruises are not treated immediately, they can cause infection and interrupt daily activities. Noni leaves are an alternative therapy containing flavonoids which play a role in anti-inflammation. This study aims to determine the effect of Noni leaf extract on bruise healing for martial arts athletes in Kedungadem District, Bojonegoro Regency. Methods: This research used a one-group pre-posttest pre-experimental design. The research sample was 32 martial arts athletes with bruises selected by Accidental sampling conducted in June - July 2023. The intervention was done by giving Noni (Morinda Citrifolia l.) leaves extract ointment for 1 week twice daily. The data were collected using an observation sheet and then tested using the McNemar test (α ≤ 0.05). Results: The results showed bruise healing in less than 7 days after Noni leaves extract therapy was given to all respondents. Noni leaf extract had an effect on bruise healing in martial arts athletes (p=0.001). Conclusions: Noni leaf ointment can significantly accelerate bruise healing without pharmacological therapy.